119 Barriers to kidney transplantation in children – a prospective national study. (December 2018) - Marlais, M; Balasubramanian, R; Sinha, MD; Marks, SD
Abstract : Introduction: Pre-emptive living donor renal transplantation is the gold standard treatment for children with end-stage kidney disease (ESKD). Despite this, many children spend years on dialysis before proceeding to transplantation. The aim of this study was to investigate access to paediatric renal transplantation and barriers within the process. Methods: This was a prospective multi-centre observational study, paediatric nephrology centres in the United Kingdom (UK) were asked to provide data on all children (aged<18 years) with ESKD (defined as estimated glomerular filtration rate ≤15 mls/min/1.73 m 2 ). In those where transplantation was not planned or delayed, barriers to transplantation and estimated timescales were documented. Results: 308 children with ESKD were included in this study from 12 out of 13 paediatric nephrology centres in the UK. 180 (58%) children were on dialysis, 37 (12%) were transplanted and 91 (29%) children had ESKD but were currently pre-dialysis. 139 (45%) were currently being worked up for a living donor transplant, 82 (27%) children were listed for a deceased donor transplant. The mean estimated time to transplant in those with active plans was 13.6 months. 226 (73%) children were not being planned for a pre-emptive transplant or were already on dialysis. Commonest reasons for children not having a pre-emptive transplant were that the child presented in ESKD (31%), lack of a suitable donor (27%) or being too young for transplant at the time of needing renal replacement therapy (24%). The commonest cited factors preventing transplantation from occurring in children were disease factors (36%), donor availability (27%) and size of the child (20%). Conclusions: Many barriers to renal transplantation in children are potentially modifiable through local or national intervention, such as donor availability and patient psycho-social factors. A further study is planned to assess these modifiable barriers to transplant in detail to determine how best to ameliorate them.